Improving Fire Resistance of Mahogany (Swietenia macrophylla) Wood Impregnated with Mixture of Borax and Boric Acid - Tomy Listyanto; Aditya Aji Pratama; Keisuke Ando; Nobuaki Hattori (Masyarakat Peneliti Kayu Indonesia, 2020)
The study was aimed to investigate the effects of mixture of borax and boric acid concentration and different level of pressure on absorption, retention quantity, and fire resistance properties of mahogany (Swietenia macrophylla). A total of 50 samples of 9 x 19 x 1016 mm (ASTM E 69-02) were taken from mahoganylumber and then air-dried. A total of 45 samples were impregnated with aqueous solutions of borax and boric acid in three different concentrations (5, 7, and 9 %) and at three different pressure levels (5, 7.5, and 10 atm) for 2 hours pressure time, while5 samples were liftedas control. Dried impregnated samples and untreated samples were feeding in flame with lid combustion method refers to ASTM E 69-02. Interestingly, the results showed that borax and boric acid effectively improved the fire resistanceproperties(mass losses, ignition temperature, maximum temperature, and smoke and smolder production)of mahogany wood.Mixtures of borax and boric acid at a concentration level of 9% and pressure of 10 atm arerecommended to obtain the best results compare to the other interactions on combustion properties.